Implementation Of Disaster Preparedness Education In Elementary Schools In Dealing With The Hazard Of Earthquakes In West Bandung Regency - Huzaefah, Ova; Jamilah, Jamilah; Syahroni, Syahroni; Artono, Artono; Ilis, N.; Lubis, Taupik; Sari, Bermara Giri Menur (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Earthquake hazard has high potential in West Bandung Regency, especially in the areas traversed by the Lembang fault (Lembang, Cisarua and Parongpong Districts). Therefore, disaster preparedness education is needed to reduce hazard, impacts, and increase the capacity of elementary school (SD). The purpose of this study was to determine the condition and level of preparedness of the elementary school in the three sub-districts in facing earthquakes based on implementation of disaster preparedness education. This study used a quantitative approach through a survey with a sample size of 118 students, 36 teachers, and 36 principals/representatives of SD in Lembang, Cisarua, and Parongpong Districts, West Bandung Regency. Measurement of preparedness is carried out by measuring the parameters of knowledge, policies and guidelines, emergency response plans, disaster warnings and resource mobilization in the elementary school then analyzed using index analysis which shows the level of preparedness of the elementary school  . The results showed that students’ preparedness falls into category prepared (index = 75.48), as well as teachers’ preparedness (index = 73.38), while the school preparedness falls into category not yet prepared (index = 31.9) and should improve its’ preparedness. These results indicate that students’ and teachers’ level of preparedness are very good although the infrastructure and the school preparedness implementation are not yet sustainable. The results also showed that the level of preparedness of the elementary school in the region falls into category of nearly prepared with an index value of 56.13. School as an institution and the whole school community should increase the level of preparedness through further study focusing in seismic study and structural or nonstructural study. Disaster preparedness in elementary school (SD) takes infrastructure support, education and institutionalization of preparedness that eventually allows the preparedness actions.